P. B. Bear's Birthday Party - Lee Davis (Italy Dorling Kindersley Limited, 1994)
P.B. Bear is a very special bear and today is a very special day. Young children are invited to join his fabulous birthday party adventure where they will: help P.B. Bear find his friends in a game of hide and seek, count the candles on his birthday cake, guess what's inside the big box, find five forks, five plates, and five party hats for the birthday picnic, and discover a tiny bear in every scene. They'll even discover what P.B. stands for!
Keywords: Read Aloud -- Read Aloud